Writing strategies by beginning authors of academic genre - Abdul Syahid (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2019)
Aimed at identifying what writing strategies four beginning authors used and examining how these strategies facilitated their writings, a collective case study describing and comparing the beginning authors was carried out to provide insights into the issue. The authors were teachers of English in English departments at four Indonesian universities, and were selected on the basis of a recommendation by the editor of some books in which their written products were published. To gain a far better understanding of the cases, two data forms (questionnaires and interview notes) were collected. The data gathered were repeatedly examined in order to discover some reoccurring patterns. The inductive process delineated the strategies used by the participants when dealing with academic writing. The results show that, in order of priority, the writing strategies employed in their initial writing careers were social, affective, compensation, and cognitive ones. This study contributes to the knowledge of social or contextual factors in writing English academic papers by illustrating which strategies were used and how in order to cope with the writing process. It also suggests writing strategies be adopted by future authors and built in the classes of English as a foreign language.